Determinant Analysis Of Fresh Demand For Exported Tuna At Bungus Ocean Fishing Port (PPS) Padang City Postpandemic Covid-19 Period - Siti Aisyah; Reffi Aryzegovina; Dicky Rustam (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
The Covid-19 pandemic is claimed to be the main cause of the decline in world trade including trade in fishery products, where the total export value of world fishery products fell by 7% compared to 2019, which was the beginning of the Covid-19 pandemic. Therefore, the determinants of demand for fresh tuna exports at PPS Bungus, Padang City, in the post-pandemic Covid-19 period need to be investigated. to maintain and increase the quantity of fresh tuna exports. Based on the description above, the purpose of this study is to analyze the determinants of domestic price factors, Japan's Gross Domestic Product (GDP), shrimp prices, and the exchange rate on demand for fresh export tuna exports at the Bungus Ocean Fishery Port (PPPS). Padang city Post-pandemic Covid-19 period. To find out how much influence the independent variables and dependent variables have in this study, the method used is multiple regression analysis. The independent variables are tuna prices (X1), Japan's GDP per capita (X2), shrimp prices (X3), exchange rates (X4), and the dependent variable is the export quantity of fresh tuna (Y). Based on the results of the study, it was concluded that the price of tuna, shrimp price and exchange rate had a positive effect on the quantity of fresh tuna exports while Japan's GDP per capita had no effect on the quantity of fresh tuna exports at the Samudera Bungus Fishery Port, Padang City